2023
DOI: 10.1177/03936155231184908
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of N6-methyladenosine-modified related chemotransferase METTL3 in gastric carcinoma: Evidence from meta-analysis

Abstract: Background N6-methyladenosine (m6A) methylation is known as the research hotspot for tumor epimodification, and its associated methyltransferase-like3 (METTL3) is significantly differentially expressed in gastric carcinoma, but its clinical value has not been summarized. This meta-analysis aimed to evaluate the prognostic significance of METTL3 in gastric carcinoma. Material and methods Databases, including PubMed, EMBASE (Ovid platform), Science Direct, Scopus, MEDLINE, Google Scholar, Web of Science, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…METTL3 has been reported to have a favourable effect on tumour growth and is a risk factor for cancer prognosis in various tumour [ 66 , 67 , 68 , 69 ]. Visvanathan et al reported a higher level of M6A modification glioma stem-like cells (GSCs) and METTL3-dependent M6A modification is crucial for GSC maintenance [ 45 ].…”
Section: M6a Methylation In Rna During Cellular Responses To Cancer R...mentioning
confidence: 99%
“…METTL3 has been reported to have a favourable effect on tumour growth and is a risk factor for cancer prognosis in various tumour [ 66 , 67 , 68 , 69 ]. Visvanathan et al reported a higher level of M6A modification glioma stem-like cells (GSCs) and METTL3-dependent M6A modification is crucial for GSC maintenance [ 45 ].…”
Section: M6a Methylation In Rna During Cellular Responses To Cancer R...mentioning
confidence: 99%